KINERJA SISTEM INFORMASI DENGAN DENGAN METODE UNIFIED MODELLING LANGUAGE - Yodhi Yuniarthe (IIB Darmajaya, 2013)
The size of the software to achieve its success is the ability to meet the needs of users with accurate data processing and display that can support a decision. One of the biggest factors in the success of software development understands the needs of the user. These needs are outlined in the features provided in the software. This paper discusses the factors that need to be considered by the information system with unified modelling language programming can contribute to the performance of the business organizations that can meet a critical factor companies that implement application programs. In this study, the expected realization of the development model of performance-based information systems software engineering methods unified modelling language that is useful for system developers to provide quality programming that is competitive to the user.Keywords— unified modelling language, performance based information systems